KINERJA BADAN KEPEGAWAIAN DAERAH DALAM REKRUTMEN CALON PEGAWAI NEGERI SIPIL DI KABUPATEN HALMAHERA SELATAN - Kajual, Betsi (JURNAL ADMINISTRASI PUBLIK, 2015)
ABSTRACTThis research entitled: Kinerja Badan Kepegawaian Daerah Dalam Rekrutmen Calon Pegawai Negeri Sipildi Kabupaten Halmahera Selatan, it means to find out performance of corporation employee province in SouthHalmahera and with the purpose to know and explain which factors that influence the performance ofcorporation employee province in recruitment of candidate the civil employee in South Halmahera.The information that acquired in this research are arranged by program of descriptive typ with thegrounded on survey and qualitative analysis whereas technic of data announcement that used by literature studyand field of study with the direct observation and interview towards to 8 informants.The results of this research in the field are indicating that since 2014-2015 years performance ofcorporation employee province in South Halmahera resulted in advancement or there are increase of theperformance, and there is some employer get the appreciation because they did their jobs and responsibilitieswith the perfection but there is so much obstacle happens when recruiting the employer candidate in SouthHalmahera.With these research, the corporation employee province in South Halmahera wishes their performancewill advance and they can implementation their duty and responsibility with good. In this case there are factorsthat obstruct performance of corporation employee province in South Halmahera recruits the employer are suitorage and they needed just some peoples, electronic facilities decrease, like computer, Wi-Fi and telephone andsome regions doesn’t have telecommunication access and using oceans strip and it takes so long. The corporationemployee province in South Halmahera wish the government of South Halmahera can looking at the things sothat the obstacles that happened by corporation employee province.Keyword :Performance Of Corporation Employee